PENGARUH MODEL PEMBELAJARAN DAN GAYA KOGNITIF TERHADAP PEMAHAMAN KONSEP DAN KEMAMPUAN BERPIKIR KRITIS - KUSMIANTI KUSMIANTI (Universitas Mahasaraswati Mataram, 2018)
This study aims to: 1). test the comparative advantage between problem-based learning model and problem solving learning model in achieving concept comprehension and critical thinking ability, 2). test the comparative advantage between students who have independent field cognitive style with students who have cognitive style field dependent in achieving conceptual understanding and critical thinking ability, 3). test the interactive influence between learning model and cognitive style to the understanding of concept and critical thinking ability. To achieve those goals, quasi experimental research is conducted on grade VIII students of SMPN 1 Suralaga. The experiment used is a two-factor measurement with a non-equivalent control group design. The results shows that 1). there is a significant difference of concept understanding between MPBM group and MPPM (F = 16,717; p <0,05). The mean value of understanding of MPBM group concept is higher than that of MPPM group (= 2,742; SD = 0.671; p <0.05). 2). there is a significant difference of conceptual understanding between the cognitive style group of FI and the cognitive style group FD (F = 51,984; p <0.05). 3). in achieving conceptual understanding, learning models and cognitive styles interacted significantly (F = 6.337; p <0.05)